Credit achievement ability during distance learning era: the case of Statistics in Medicine course - Stura, Ilaria; Alemanni, Alessandra; Migliaretti, Giuseppe (Journal of Biomedical Practitioners, 2021)
AIM In this study, the effects of the DL on academic career were investigated. BACKGROUND Distance Learning (DL) became mandatory in Italy from March 2020, due to COVID19 emergency. DESIGN The performances of students in Medical Statistics course of the Nursing degree in three campus of the University of Turin (Aosta, Beinasco and Cuneo) in the Academic Years 2019-2020 and 2020-2021 were considered. METHODS The study is based on 308 students, 48% of whom both attended the lessons and took the exams in DL. The effect of DL on student’s performance was evaluated using Logistic regression models and the results are showed in terms of odds ratios adjusted for gender, age and campus. RESULTS The results show that DL did not bring particular limitations to the students, highlighting on the contrary evident benefits in terms of organization and management of lessons and exams. Moreover, the level of students’ satisfaction at the end of the course increased in DL. CONCLUSION DL seems to do not affect the student’s ability on achieve credits, at least in mathematical subjects. More investigations are needed considering all courses’ types.